Governing Risks in Modern Britain Danger, Safety and Accidents, c. 1800-2000 - Crook, Tom.; Esbester, Mike.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
For more than 200 years, everyday life in Britain has been beset by a variety of dangers, from the mundane to the life-threatening. Governing Risks in Modern Britain focuses on the steps taken to manage these dangers and to prevent accidents since approximately 1800. It brings together cutting-edge research to help us understand the multiple and contested ways in which dangers have been governed. It demonstrates that the category of 'risk', broadly defined, provides a new means of historicising some key developments in British society. Chapters explore road safety and policing, environmental and technological dangers, and occupational health and safety. The book thus brings together practices and ideas previously treated in isolation, situating them in a common context of risk-related debates, dilemmas and difficulties. Doing so, it argues, advances our understanding of how modern British society has been governed and helps to set our risk-obsessed present in some much needed historical perspective.
Keywords: Great Britain-History.; Civilization-History.; Cultural History